THE EFFECT OF THE PARAMETERS DEVIATIONS OF THE TRACTION MOTORS ON THE QUALITY OF SWITCHING DURING TRANSIENTS TAKING INTO ACCOUNT THE WEAKENED FIELD - Dubinets, L. V.; Shapovalov, A. V. (Science and Transport Progress, 2009)
In the paper the dependence of tractive engine sparking degree on practical realization of deviations of geometric parameters of additional poles magnetic circuit under transient process related to the loss of feed and its further restoration during the weakened field is demonstrated.